QIRAAH DALAM PANDANGAN ATH-TABARI - Rohmah, Umi Nuriyatur; Roziqin, Ahmad Khoirur (LPPM Sekolah Tinggi Ilmu Al-Qur'an Wali Songo Situbondo, 2022)
Ibn Jarir al-Thabari is a Qur'anic scholar who specializes in qiraah and Qur'anic sciences. In the field of tafsir, he has a spectacular tafsir titled jami 'al-Bayan fi Tafsir al-Qur'an, in which he uses qiraah to interpret the verses of the Qur'an, and the understanding of qira'at al-Thabari has a significant impact on the results of his interpretation. As a result, the purpose of this study is to ascertain the meaning of qiraah al-Thabari and its impact on the interpretation of Qur'anic verses in tafsir jami 'al-Bayan fi Tafsir al-Qur'an. As a consequence of this research, al-Thabari has numerous criteria that must be followed when picking qiraah, including the legitimacy of the chain, conformity to the Arabic language, and adherence to Ottoman tradition. Al-Tabari is quite picky about which qiraah references he uses in his interpretation. As a result, qiraah mutawatirah pays him close attention. According to Al-Tabari, qiraah mutawatirah must extend all the way to the source of qiraah. Qiraah mutawatirah must be supported by a chain of sanad that truly relies on the qiraah priest and on traditions that have well-known reputation, can be trusted, and must be absolutely muttasil with the Prophet Muhammad SAW as a person who received revelation from the Koran.